Going to the Sea Park - Mayer, Mercer, 1943- (New York : Harper, 2009)
Little Critter and his classmates are taking a trip to the Sea Park. Join Little Critter as he learns about exciting and strange sea creatures.
"Mercer Mayer's Little Critter"--Cover.
"My first I can read book"--Spine.
"Ages 3-5"--Jacket.
Keywords: Little Critter -- (Fictitious character) -- Juvenile fiction; School field trips -- Juvenile fiction; Public aquariums -- Juvenile fiction; Schools -- Juvenile fiction